Metode Cogeneration untuk Efisiensi Gas Turbine Generator 3x108 MW pada PLTGU Blok II PT. PLN Indonesia Power UBP Semarang - Firdaus Rizaldi; Muhamad Haddin (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
The low thermal efficiency of Gas Power Plants (PLTG) due to exhaust gas heat loss drives the implementation of cogeneration at PLTGU Block II PT. PLN Indonesia Power UBP Semarang. This study analyzes the performance of the Gas Turbine Generator (GTG), combined cycle efficiency, and Exergy distribution using a 3-3-1 configuration. The research utilizes actual operational data from January 28, 2026, sampled at 10-minute intervals. Results indicate that cogeneration via a Heat Recovery Steam Generator (HRSG) significantly enhances plant efficiency. The GTG output ranged from 273–283 MW with an efficiency of 30.0–30.2%. Following combined cycle integration, system efficiency increased to 43.9–44.4%, a gain of approximately 14%, with a heat rate of 11,916–11,988 kJ/kWh. Exhaust heat of 665–713 MW was recovered to generate an additional 130 MW through the Steam Turbine Generator (STG). Exergy analysis reveals that the largest irreversibility occurs in the GTG combustion process (285 MW), followed by the HRSG (185 MW) and STG (49 MW).